Education Reform Towards the Future Development of Nation - Devit Etika Sari (STAI Miftahul Ula Nganjuk, 2019)
Global era is a challenge for seizing competitive quality among nations. The challenge Become an agenda for an education system Realizing Able to answer some requirement for development. Education is the main pillar of development Actually, functional decadence of education h 9Ccurred within erosion in the process of striking objective of education: Reformation is urgent, in terms of education system, the learning of personal education, the existence of education personals. Reformation in the three elements should be synergic and progressing mission / visions for education leading to the purpose of human development, generating human who are intelligent, Piety, scholarly, humanistic, adaptive, independent, moralized, fair, and populism. Some effort for Realizing the objectives are the responsibility of government, schools and society. Thought this writing, it is Discussed some issues of education reformations by converting aspects of institutions, professionalism of education personals, and their relation to the future development of Nations